The Influence of Selected Demographic Factors on Depression among Working Women in Higher Education Institutions - Deepthi. M; Niviya Feston; Krishnamurthy V. S. (Journal of Psychology and Social Sciences, 2026)
The present study examined the association between socio-demographic factors, depression, and sleep quality among working women in higher education institutions. A cross-sectional survey design was employed, and data were collected from 300 female faculty members using the Beck Depression Inventory (BDI) and the Pittsburgh Sleep Quality Index (PSQI). Descriptive statistics, chi-square tests, and multiple regression analyses were conducted to examine relationships between socio-demographic variables and mental health outcomes. Chi-square analyses revealed that educational qualification and type of appointment were significantly associated with levels of depression, while sleep quality was significantly associated with age, educational qualification, designation, teaching experience, type of appointment, marital status, and socio-economic status. Multiple regression analysis indicated that educational qualification and socio-economic status significantly predicted depression, accounting for a modest proportion of variance. In contrast, the regression model predicting sleep quality was statistically significant, explaining over half of the variance, with educational qualification, type of appointment, marital status, and socio-economic status emerging as significant predictors. The findings highlight the differential impact of socio- demographic and occupational factors on depression and sleep quality among working women. Interventions focusing on employment stability, workload management, and psychosocial support may be critical in promoting mental health and sleep well-being in academic work settings.